Pulmonary Surfactant Surface Tension Influences Alveolar Capillary Shape and Oxygenation - Ikegami, Machiko (American Thoracic Society, 2009)
Alveolar capillaries are located in close proximity to the alveolar epithelium and beneath the surfactant film. We hypothesized that the shape of alveolar capillaries and accompanying oxygenation are influenced by surfactant surface tension in the alveolus. To prove our hypothesis, surfactant surface tension was regulated by conditional expression of surfactant protein (SP)-B in Sftpb(−/−) mice, thereby inhibiting surface tension–lowering properties of surfactant in vivo within 24 hours after depletion of Sftpb. Minimum surface tension of isolated surfactant was increased and oxygen saturation was significantly reduced after 2 days of SP-B deficiency in association with deformation of alveolar capillaries. Intravascularly injected 3.2-μm-diameter microbeads through jugular vein were retained within narrowed pulmonary capillaries after reduction of SP-B. Ultrastructure studies demonstrated that the capillary protrusion typical of the normal alveolar–capillary unit was reduced in size, consistent with altered pulmonary blood flow. Pulmonary hypertension and intrapulmonary shunting are commonly associated with surfactant deficiency and dysfunction in neonates and adults with respiratory distress syndromes. Increased surfactant surface tension caused by reduction in SP-B induced narrowing of alveolar capillaries and oxygen desaturation, demonstrating an important role of surface tension–lowering properties of surfactant in the regulation of pulmonary vascular perfusion.